Literatura infantil e língua portuguesa: as histórias infantis como estímulo para leitura e escrita nos anos iniciais do ensino fundamental - SANTOS, Wellington Nunes dos (2024)
This article deals with a study on the contribution of Children's Literature in the development and acquisition of Reading and Writing in the early grades of Elementary School, having children's stories as a stimulus for an improvement and development of the habit of reading and writing, reflecting on the its importance for a more pleasant, exciting and interesting teaching and learning method in the school environment. This study addressed Oral and Written Languages ​​as well as Reading, and its importance in the process of better comprehension and understanding of knowledge. Among the authors who guided this bibliographic research are: ABRAMOVICH (2006); ZILBERMAN (1998); LAJOLO (1983); VYGOTSKY (1991). We sought to understand the teaching methods used and how they can help in the acquisition of skills and abilities in the educational field. At the end of this work, a discussion was made on Children's Literature as a Stimulus in the Teaching of Reading and Writing, which can be a great ally, helping and facilitating learning, in addition to developing imagination, creativity and developing the pleasure of reading and written.